Animal tracing with sulfur isotopes: Spatial segregation and climate variability in Africa likely contribute to population trends of a migratory songbird - Brlík, Vojtěch; Procházka, Petr; Hansson, Bengt; Stricker, Craig A; Yohannes, Elizabeth; Powell, Rebecca L; Wunder, Michael B (The Journal of animal ecology, 2023)
Climatic conditions affect animals but range-wide impacts at the population level remain largely unknown, especially in migratory species. However, studying climate-population relationships is still challenging in small migrants due to a lack of efficient and cost-effective geographic tracking method. Spatial distribution patterns of environmental stable isotopes (so called 'isoscapes') generally overcome these limitations but none of the currently available isoscapes provide a substantial longitudinal gradient in species-rich sub-Saharan Africa. In this region, sulphur (δ34 S) has not been sufficiently explored on a larger scale. We developed a δ34 S isoscape to trace animal origins in sub-Saharan Africa by coupling known-origin samples from tracked migratory birds with continental remotely sensed environmental data building on environment-δ34 S relationships using a flexible machine learning technique. Furthermore, we link population-specific nonbreeding grounds with interannual climatic variation that might translate to breeding population trends. The predicted δ34 S isotopic map featured east-west and coast-to-inland isotopic gradients and was applied to predict nonbreeding grounds of three breeding populations of Eurasian Reed Warblers Acrocephalus scirpaceus with two distinct migratory phenotypes. Breeding populations as well as migratory phenotypes exhibited large-scale segregation within the African nonbreeding range. These regions also differed substantially in the interannual climatic variation, with higher interannual variability in the eastern part of the range during 2001-2012. Over the same period, the eastern European breeding population seemed to have experienced a more steep decline in population size. The link between migratory patterns and large-scale climatic variability appears important to better understand population trajectories in many declining migratory animals. We believe animal tracing using sulphur isotopes will facilitate these efforts and offers manifold ecological and forensic applications in the biodiversity hotspot of sub-Saharan Africa.
Keywords: Population Density; sulphur; migrace zvířat; tracing; hustota populace; Songbirds; Sulfur Isotopes; zvířata; migratory divide; Africa; izotopy síry; roční období; Afrika; migration; Animal Migration; Seasons; zpěvní ptáci; isoscape; tracking; Animals; remote sensing; climate variability